2013
DOI: 10.1038/cr.2013.120
|View full text |Cite
|
Sign up to set email alerts
|

A novel partner of Scalloped regulates Hippo signaling via antagonizing Scalloped-Yorkie activity

Abstract: The Hippo (Hpo) pathway controls tissue growth and organ size by regulating the activity of transcriptional co-activator Yorkie (Yki), which associates with transcription factor Scalloped (Sd) in the nucleus to promote downstream target gene expression. Here we identify a novel protein Sd-Binding-Protein (SdBP)/Tgi, which directly competes with Yki for binding to Sd through its TDU domains and inhibits the Sd-Yki transcriptional activity. We also find that SdBP retains Yki in the nucleus through the associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
93
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(101 citation statements)
references
References 47 publications
8
93
0
Order By: Relevance
“…Sd Binding Protein (SdBP)/Tgi, the Drosophila homologue of VGLL4, interacts with Sd through its TDU domains and competes with Yki in nucleus to restrict tissue growth [45]. It is worth noting that Tgi is slightly different from VGLL4 with three extra PPxY motifs, which are essential for Tgi-Yki binding.…”
Section: Discussionmentioning
confidence: 99%
“…Sd Binding Protein (SdBP)/Tgi, the Drosophila homologue of VGLL4, interacts with Sd through its TDU domains and competes with Yki in nucleus to restrict tissue growth [45]. It is worth noting that Tgi is slightly different from VGLL4 with three extra PPxY motifs, which are essential for Tgi-Yki binding.…”
Section: Discussionmentioning
confidence: 99%
“…How does the antagonistic effect of Ci on Hpo activity contribute to Yki signal transduction in ECs? Previous studies have suggested that only a low level of nuclear Yki is sufficient to maintain normal tissue growth by antagonizing Sd-mediated default repression [24,25]. However, this amount of nuclear Yki could be very sensitive to Hpo activation when cells respond to environmental cues during development.…”
Section: Discussionmentioning
confidence: 83%
“…Recent studies have identified Tgi, a Tondu-domain-containing protein, as an Sd cofactor in the default repressing complex to regulate tissue growth in Drosophila imaginal discs [24,25]. We followed the above protocol to test whether Tgi contributes to the Sd-mediated default repression in ECs.…”
Section: The Tondu-domain-containing Proteins Suppress Germ Cell Diffmentioning
confidence: 99%
See 1 more Smart Citation
“…In this model Tgi/SdBP suppresses tissue growth participating in the Hippo pathway by interfering with targets transcription (Guo et al, 2013, Koontz et al, 2013.…”
Section: Vgll4 Gene Expression In Xenopus Embryogenesis 375mentioning
confidence: 99%